Dataset on the concentrations of anticoagulant rodenticides in raptors from the Canary Islands with geographic information - Cristian Rial-Berriel (Data in Brief, 2021)
The dataset presented in this article supports “Intensive livestock farming as a major determinant of the exposure to anticoagulant rodenticides in raptors of the Canary Islands (Spain)” (Rial-Berriel et al., 2020). A Geographic Information System (GIS) analysis on the influence of the influence of livestock activity on exposure to anticoagulant rodenticides in raptors in the Canary Islands was performed. This dataset provides geographic information on the localization of each raptor (either positive or negative for anticoagulant rodenticides, n = 308), as well as the concentrations of each compound found in their livers. In addition, we present complementary analyses to those included in the main article, such as the detailed analysis of the farming activity influence on anticoagulant rodenticide exposure of raptors, by island and by raptor species.